2013
DOI: 10.1063/1.4794017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blast wave re-focusing on a laser-induced plasma

Abstract: The effect of laser-induced plasma confinement on lifetime and temperature is reported using cylindrical reflectors. This is determined experimentally in a gas cell, with hydrogen as test gas, and cylindrical shock reflectors of different diameters. The temperature evolution of confined and unconfined laser-induced plasma has been measured using plasma emission spectroscopy. Temperatures were determined through the plasma line-to-continuum thermometry technique in the hydrogen Balmer series using the H a and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It was thought during the design phase of the experiment that the cylindrical geometry of the injector would focus the blast wave back into the plasma and increase the plasme temperature still further. Plasma temperature measurements in a static cell [6] showed that this was indeed the case, but that the temperature enhancement lasted for less than 700 ns, a much shorter period than the time required for the plasma to reach the shear layer. The OH signal for the fuel-jet configuration was significantly enhanced by adding argon because the argon can remain ionized for longer than hydrogen, as more electrons can be removed from the outer shell of the noble gas atom.…”
Section: Laser Spark Experiments In a Model Scramjetmentioning
confidence: 92%
“…It was thought during the design phase of the experiment that the cylindrical geometry of the injector would focus the blast wave back into the plasma and increase the plasme temperature still further. Plasma temperature measurements in a static cell [6] showed that this was indeed the case, but that the temperature enhancement lasted for less than 700 ns, a much shorter period than the time required for the plasma to reach the shear layer. The OH signal for the fuel-jet configuration was significantly enhanced by adding argon because the argon can remain ionized for longer than hydrogen, as more electrons can be removed from the outer shell of the noble gas atom.…”
Section: Laser Spark Experiments In a Model Scramjetmentioning
confidence: 92%
“…This approximate estimate is based on measurements of plasma kernels reported in the literature. 18,29,30 The focusing optics of the LIBS laser (and LIBS trigger timing) were aligned to maximize the spatiotemporal overlap between the microplasma and the path of the falling particles (as defined by the entry inlet of ∼1.5 mm diameter at top of apparatus). Given these dimensions, we estimate that the plasma covers approximately 45% of the projected area of the falling aerosol stream.…”
Section: Methodsmentioning
confidence: 99%
“…5 Electric discharge is the most common external ignition aid in previous studies, but a repetitively pulsed, Q-switched laser can also be used to generate plasma non-intrusively by placing the focus of the beam inside the flow path. An experimental investigation of a technique such as this is documented in Brieschenk et al 2,3,4 who studied the behaviour of hydrogen jets in hypersonic crossflow and their interaction with laser-induced-plasma (LIP). Time resolved imagery of the ignition process detected the signature of preflame formation, but no stabilized hot flame was formed.…”
Section: Introductionmentioning
confidence: 98%